Multi-Scenario Simulation of the Dynamic Relationship Between Land Use and Carbon Storage in the Urbanization Process: A Case Study of Zhengzhou, China - Qianqian Zhang; Siyuan Liu; Yilin Niu; Yajin Hu; Ling Li; Enxiang Cai; Yali Zhang; Menglong Zhao (Land, 2025)
Rapid urbanization enhances the necessity of exploring sustainable development paths to achieve ecological and carbon storage protection. This study takes Zhengzhou, one of the national central cities in China, as a case to investigate the dynamic correlation between urbanization (UR) and carbon storage (CS). The PLUS and InVEST models were employed to simulate land use and carbon storage dynamics under natural development, cultivated land protection, and ecological protection scenarios for 2030 and 2040. This was also complemented by elasticity analysis of UR, construction land expansion (CEL), and CS. The results show that from 2000 to 2020, cultivated land declined by 15.33%, while construction land expanded by 13.31%. By 2030, construction land growth is expected to be 7.34%, 2.87%, and 4.96% across scenarios, with cultivated land of −6.96%, −2.36%, and −4.78%, respectively. Carbon storage in 2030 decreases under all scenarios (5.181 × 107 t, 5.235 × 107 t, 5.209 × 107 t) but stabilizes by 2040, with ecological protection enhancing forest/water bodies and mitigating losses. Elasticity analysis reveals that unconstrained elasticity coefficient significantly exacerbates carbon losses, while policy interventions reduce losses through expansion control and carbon sequestration. Integrating land use policies to balance farmland protection, ecological restoration, and low-carbon urban expansion is critical for sustainable megacity development and a scalable framework for carbon governance.